Soil mechanics : calculations, principles, and methods - Kaliakin, Victor N. (Butterworth-Heinemann is an imprint of Elsevier, 2017)
This book provides expert insights into the nature of soil mechanics through the use of calculation and problem-solving techniques. This informed reference begins with basic principles and calculations, illustrating physical meanings of the unit weight of soil, specific gravity, water content, void ratio, porosity, saturation, and their typical values. This is followed by calculations that illustrate the need for soil identification, classification, and ways to obtain soil particle size distribution, including sizes smaller than 0.075mm, performance, and the use of liquid and plastic limit tests. The book goes on to provide expert coverage regarding the use of soil identification and classification systems (both Unified Soil Classification System and AASHTO), and also includes applications concerning soil compaction and field applications, hydraulic conductivity and seepage, soil compressibility and field application, and shear strength and field application--